Information modelling and knowledge bases XXI - Welzer, Tatjana, 1961- (Frontiers in artificial intelligence and applications, 2010)
Drawing together researchers and practitioners from the field, European-Japanese conferences aim to advance research into, and the application of, information modelling and knowledge bases. This title contains papers presented at the 19th European-Japanese Conference on information modelling and knowledge bases (EJC 2009).